Application of the K-Means Method in Determining the Clustering of the Economic Status of the Villagers of Gunung Megang - Edison Edison; Yupianti Yupianti; Lena Elfianty (Penerbit Jurnal Indonesia, 2021)
Gunung Megang Village is one of the villages located in Semidang Alas District, Seluma Regency. Every year the Village Head will record the population for data archiving and reporting, where the process has utilized a computerized system, namely by using office applications. However, the current population data collection only records the number of residents in Gunung Megang Village (data attached), so it cannot find out population information based on economic status. Economic status is the position of a person or family in society based on monthly income. However, the economic capacity of each community is different, some have a high economic status and some have a low one, this is seen in terms of income and expenditure. The application for determining the clustering of the economic status of the residents of Gunung Megang Village was made using the Visual Basic .Net programming language and SQL Server 2008 Database by applying one of the data mining methods used, K-Means. The grouping is based on data on the economic status of the residents of Gunung Megang Village (data attached) which is divided into 3 clusters, namely Cluster 1 (High), Cluster 2 (Medium) and Cluster 3 (Low). With this application, it is hoped that it can help the Gunung Megang Village Office in finding out information on the economic status of the population. Based on the tests that have been carried out, the functionality of the application for determining the clustering of the economic status of the residents of Gunung Megang Village is running as expected, and the application is able to provide information on the grouping of data on the economic status of the residents of Gunung Megang Village.